Pengaruh Penggunaan Media Pembelajaran Nearpod dan Kemandirian Belajar Terhadap Kemampuan Pemecahan Masalah Matematis - Alpi Mulyani; Dani Firmansyah (Jurnal Didactical Mathematics, 2025)
This study aims to determine the effect of using Nearpod learning media and the level of learning independence on students' mathematical problem-solving abilities. The study uses a quantitative approach with a factorial experimental design, involving 30 students randomly selected from the research population. The instruments used consist of a mathematical problem-solving ability test in essay form and a Likert scale learning independence questionnaire. Data analysis was conducted using a Two-Way ANOVA test with the assistance of SPSS Statistics 25. The results of the study indicate that (1) there is a significant effect of the use of Nearpod learning media on students' mathematical problem-solving abilities, with higher average scores compared to other groups; (2) there was a significant effect of learning independence level on mathematical problem-solving ability, with students with high independence achieving better results; and (3) there was no significant interaction between the use of Nearpod learning media and learning independence level on mathematical problem-solving ability. These findings indicate that Nearpod and learning independence each contribute to students' abilities, but do not interactively influence one another.